Preparing Copper Nanoparticles and Flexible Copper Conductive Sheets - Gui-Bing Hong; Jia-Fang Wang; Kai-Jen Chuang; Hsiu-Yueh Cheng; Kai-Chau Chang; Chih-Ming Ma (Nanomaterials, 2022)
Nanotechnology is used in a wide range of fields, including medicine, cosmetics, and new material development, and is one of the most popular technologies in the field of flexible electronic products. For the present work, the chemical reduction method with environmentally friendly reducing agents was used to synthesize copper nanoparticles (CuNPs) with good dispersibility. The CuNPs were characterized by transmission electron microscopy (TEM), X-ray diffraction (XRD), and ultraviolet–visible spectrophotometry (UV–vis). After the CuNPs were formed, the solvent, polymers, and additives were added to form copper ink. Finally, the prepared copper inks were applied to flexible polyethylene terephthalate (PET) substrate under low sintering temperature and the effects of sintering time and different concentrations of sintering agent on resistivity were investigated. The results show that the copper nanoparticles synthesized by secondary reduction were smaller, more uniform, and better dispersed than those formed by primary reduction. Ethylene glycol has reducing effects under high temperatures; therefore, the CuNPs formed using the mixed solvent were small and well dispersed. The copper ink was applied on the PET substrate, treated with a formic acid aqueous solution, and sintered at 130 °C for 60 min, and its resistivity was about 1.67 × 10−3 Ω cm. The proposed synthesizing method is expected to have potential applications in the flexible electronic products field.